The impact of chat language in writing among secondary school students in Sandakan - Loh, Monica Pui Ling (2007)
This study discusses interaction on 'Internet Relay Chat', the synchronous computermediated communication system available on the internet. This paper studies the linguistic characteristics of the new medium of synchronous computer-mediated communication called Internet Relay Chat (IRC). With thousands of people using it from all over the world at any time, IRC is undoubtedly one of the most popular chat systems in the world today. Malaysian teenagers are no exceptions to the exposure of this new technology. This research is focused predominantly on the ethnographic and communicational aspects of IRC such as its characteristics, mixing languages while chatting and its impact on Englis h Language Usage. The study focused on Form Four and Form Five students from three secondary schools in Sandakan. The results of the study have shown the special characteristics of IRC that is the usage of short forms, abbreviations, acronyms, emoticons and slang which are understood by chatters all over the world. The findings also revealed that a considerable amount of code switching occur among Malaysian students during chat. Nevertheless, there is the fear that chat language may penetrate and have a negative influence on formal writing in the future.